(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article examines the clinical specifics and pathogenetic mechanisms underlying the optimization of dental treatment in patients with chronic renal failure (CRF) accompanied by inflammatory lesions of the oral mucosa. The analysis is based on a synthesis of empirical data demonstrating that CRF induces systemic dysregulation of immune and metabolic pathways, which significantly alters the morphology and function of the oral tissues. Persistent xerostomia, shifts in the biochemical composition of saliva, and salivary protein imbalance lead to the destabilization of local defense mechanisms. Histologically, oral mucosal inflammation in CRF patients is characterized by atrophic epithelial changes, microvascular disturbances, and impaired reparative responses. The prevalence and severity of gingivitis, stomatitis, and non-carious cervical lesions correlate with residual renal function, dialysis modality, and the presence of endocrine comorbidities. Dental hard tissues exhibit structural degradation, including enamel demineralization and dentin sclerosis, with altered elemental ratios. The study substantiates the necessity of individualized treatment protocols, incorporating pre-dialysis planning, management of odontogenic infection foci, and modulation of inflammatory activity with non-nephrotoxic agents. The proposed therapeutic model emphasizes interdisciplinary coordination between dentistry and nephrology to mitigate systemic complications and preserve oral functionality.